Proust as Musician - Nattiez, Jean-Jacques 1945-; Puffet, Derrick (Cambridge Cambridge University Press, 1989)
Throughout A la recherche du temps perdu, and particularly Swann in Love, Proust displays a surprising sensitivity to the way music is heard, a sensitivity to which we owe some of the most beautiful writing on music. Music as a model for literature: this is the subject of Nattiez's book, which unravels the various musical themes running through Proust's work, and which constitutes a particularly lucid and perceptive introduction to his writing. Through a study of the texts devoted to the Sonata and Septet of Vinteuil, the author demonstrates the fundamental role played by music in the evolution of the novel, and shows how Debussy, Wagner, and Beethoven provide the basis for a mystical quest whose goal is pure music and the literary absolute.
Keywords: Proust, Marcel -- 1871-1922; Beethoven, Ludwig van -- 1770-1827; Wagner, Richard -- 1813-1883; Debussy, Claude -- 1862-1918; Music philosophy and esthetics; Literature